(untitled) (Agricultural Engineering, 2020)
Modern livestock facilities necessary in the production of milk, meat or other animal products should be constructed with environmental protection in mind, while ensuring high quality of production and animal welfare. The high level of mechanization in modern dairy farms, including automated and robotic processes, allows obtaining high quality raw material (e.g. milk), and significantly increasing labor and production efficiency. In addition, the use of photovoltaic (PV) panels, heat recovery from milk and obtaining biogas from the manure fermentation process, contributes to large energy savings on the farm. Excess of natural fertilizers, which are an animal byproduct, can be used as a substrate for methane fermentation. The presented examples of obtaining renewable energy allow improving the economic efficiency of animal production. They also ensure appropriate environmental conditions through the innovative management of natural fertilizers.